The Urokinase Receptor Homolog Haldisin Is a Novel Differentiation Marker of Stratum Granulosum in Squamous Epithelia - Gårdsvoll, Henrik (SAGE Publications, 2013)
Several members of the Ly-6/uPAR (LU)-protein domain family are differentially expressed in human squamous epithelia. In some cases, they even play important roles in maintaining skin homeostasis, as exemplified by the secreted single domain member, SLURP-1, the deficiency of which is associated with the development of palmoplantar hyperkeratosis in the congenital skin disorder Mal de Meleda. In the present study, we have characterized a new member of the LU-protein domain family, which we find to be predominantly expressed in the stratum granulosum of human skin, thus resembling the expression of SLURP-1. In accordance with its expression pattern, we denote this protein product, which is encoded by the LYPD5 gene, as Haldisin (human antigen with LU-domains expressed in skin). Two of the five human glycolipid-anchored membrane proteins with multiple LU-domains characterized so far are predominantly confined to squamous epithelia (i.e., C4.4A), to stratum spinosum, and Haldisin to stratum granulosum under normal homeostatic conditions. Whether Haldisin is a prognostic biomarker for certain epithelial malignancies, like C4.4A and SLURP-1, remains to be explored.